Study on Flame Retardancy of Cotton Fabric Modified by Sulfonic Groups Chelated with Ba2+ - Lingling Guo; Hongqin Lin; Zhenming Qi; Jiang Pan; Haiyan Mao; Chunmei Huang; Guoqiang Li; Chunxia Wang (Molecules)
A simple and innovative method was introduced for the production of green and recoverable flame-retardant cotton fabrics, where sulfonated cotton fabric (COT-SC) was synthesized by oxidizing cotton fabric with sodium periodate, followed by a sulfonation step with sodium bisulfite to provide active sites, which further chelated barium ions (Ba2+) to achieve flame retardancy. The morphological and structural characterizations of the fabricated cotton fabrics (COT-SC-Ba) demonstrated that the cleavage of C2-C3 free hydroxy groups within the cellulose macromolecule was chemically modified for grafting a considerable number of sulfonic acid groups, and Ba2+ ions were effectively immobilized on the macromolecule of the cotton fabric through a chelation effect. Results from cone calorimeter tests (CCTs) revealed that COT-SC-Ba became nonflammable, displayed a delayed ignition time, and decreased the values of the heat release rate (HRR), total smoke release (TSR), effective heat of combustion (EHC), and CO/CO2 ratio. TG/DTG analysis demonstrated that COT-SC-Ba possessed greater thermal stability, fewer flammable volatiles, and more of a char layer during burning than that of the original cotton fabric. Its residual mass was increased from 0.02% to 26.9% in air and from 8.05% to 26.76% in N2, respectively. The COT-SC-Ba not only possessed a limiting oxygen index (LOI) of up to 34.4% but could also undergo vertical burning tests evidenced by results such as the non-afterflame, non-afterglow, and a mere 75 mm char length. Those results demonstrated that the combination of SO3− and Ba2+ promoted the formation of a char layer. Moreover, cotton fabric regained its superior flame retardancy after being washed and re-chelated with Ba2+. Additional characteristics of the cotton fabric, such as the rupture strength, white degree, and hygroscopicity, were maintained at an acceptable level. In conclusion, this research can offer a fresh perspective on the design and development of straightforward, efficient, eco-friendly, and recoverable fire-retardant fabrics.